Litanies, Vespers [de Wolfgang Amadeus Mozart] = Shorter Sacred Works = Kleinere Kirchenwerke [de Wolfgang Amadeus Mozart] = Litanies, Vêpres et motets sacrés [de Wolfgang Amadeus Mozart] = Litanie, vespri e altri pezzi sacri [de Wolfgang Amadeus Mozart] - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: KV 109, KV 243, KV 321, KV 125, KV 195, KV 193, KV 339, KV 341, KV 618, KV 165, KV 33, KV 90, KV 91, KV 20, KV 34, KV 44, KV 47, KV 72, KV 85, KV 86, KV 108, KV 117, KV 322, KV 323, KV 127, KV 141, KV 143, KV 198, KV 222, KV 260, KV 273, KV 276, KV 277.